Development Material Test Face Makeup Competency Daily On Vocational Students Skills Program Rules of Beauty - Windayani, Novia Restu; Qudus, Nur; Widjanarko, Dwi (Journal of Vocational and Career Education, 2018)
Competency test material is an integral part of an assessment in learning process. What is to be measured in learning and the availability of instrument. The purpose of the study is to analyze the validity of competency test material, the reliability of the test material, and to determine the effectiveness of competency test material. This study employed research and development (R & D) method. The product developed in this study was the daily make up competency test material validated by using expert validation, and has been tested on students of the beauty program in vocational high school in May 2018. The validity of the product was achieved by using validity test, reliability by reliability test and effectiveness of competency test material using normalized-gain test analysis. The results of the study on the development of daily makeup competency test materials for vocational school students in beauty program showed that there were 3 aspects of assessments: knowledge, attitudes and skills. The effectiveness of knowledge competency test material was 20%; attitude 35%; and skill 85%. The testing material was proven to be able to assess students effectively and objectively.